An approach to the approximation of the inverse of a square matrix by He’s homotopy perturbation method - Keramati, B. (Italian Journal of Pure and Applied Mathematics, 2011)
In this paper, we present an efficient numerical algorithm for approximating the inverse of a square matrix based on homotopy perturbation method. Some numerical illustrations are given to show the effciency of the algorithm. of the algorithm.